Paragraph writing by students taking The Malaysian University English Test (MUET) in a Malaysian secondary school / Lendik Mawin @ Lendik Edmond Mawin - Mawin @ Edmond Mawin, Lendik (2008)
This study investigates the factors affecting paragraph writing among Sixth Form MUET students in SMK Muara Tuang, Kota Samarahan, Sarawak. Writing is a skill that students have to master in order to do well in their studies at colleges or universities. Various variables were identified in order to find the causes of students’ poor performance in writing, particularly in paragraph writing, which forms the basis for other writing tasks such as writing essays and reports. These variables include the students’ background, interest in learning the English language, attitudes, habits and abilities in both reading and writing. To identify the factors, questionnaires were distributed to 200 Sixth Form students. Apart from that, the students were also required to write a paragraph of 100-150 words, which formed a small corpus that was used to identify the various errors that the students made in their writing. Data collected from both these instruments were analysed in order to determine the factors that affect their paragraph writing. The study revealed that the students did not do well in their writing and the major factors that contributed to their poor performance were: lack of English reading materials especially at home, negative attitude towards reading and writing in English, poor command of grammar and vocabulary, poor skill in generating ideas, writing introductions, topic sentences, supporting details, transitional sentences and concluding sentences. Nevertheless, the students were found to have a good interest in learning English. Therefore, it is vital for all parties, namely, parents and teachers to put a concerted effort in order to improve the students’ writing.